Transcriptomics Analysis and Re-sequencing Reveal the Mechanism Underlying the Thermotolerance of an Artificial Selection Population of the Pacific Oyster - Tan, Yulong; Cong, Rihao; Qi, Haigang; Wang, Luping; Zhang, Guofan; Pan, Ying; Li, Li (Frontiers in Physiology, 2021)
The Pacific oyster is a globally important aquaculture species inhabiting the intertidal environment, which experiences great temperature variation. Mass deaths in the summer pose a major challenge for the oyster industry. We initiated an artificial selection breeding program in 2017 using acute heat shock treatments of the parents to select for thermotolerance in oysters. In this study, we compared the respiration rate, summer survival rate, gene expression, and gene structure of F2 selected oysters and non-selected wild oysters. A transcriptional analysis revealed global divergence between the selected and control groups at the larval stage, including 4764 DEGs, among which 79 genes were heat-responsive genes. Five heat shock proteins were enriched, and four of the six genes (five heat stock genes in the enriched GO terms and KEGG pathways and BAG4) were differentially expressed in one-year-old oysters. Integration of the transcriptomic and re-sequencing data of the selected and the control groups revealed 1090 genes that differentiated in both gene structure and expression. Two SNPs that may mediate the expression of CGI_10022585 and CGI_10024709 were validated. In addition, the respiration rate of one-year-old oysters varied significantly between the selected group and the control group at room temperature (20 ℃). And the summer survival rate of the selected population was significantly improved. This study not only shows that artificial selection has a significant effect on the gene structure and expression of oysters, but it also helps reveal the mechanism underlying their tolerance of high temperature as well as the ability of oysters to adapt to climate change.